KONTROL DIRI SEBAGAI MEDIASI PENGARUH PENGGUNAAN UANG ELEKTRONIK, GAYA HIDUP, DAN KONFORMITAS TERHADAP PERILAKU KONSUMTIF GENERASI Z KOTA DEPOK - Nabila, Shofiyyatun; Trihudiyatmanto, M.; Efendi, Bahtiar (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study to determine electronic money usage, lifestyle and conformity to consumptive behavior through self-control. This study also examines how conformity plays an important role in consumption behavior of generation Z who tends to follow peer group trends. Population in this study is generation Z in Depok City aged 17-27 years. The sample amounted to 189 respondens obtained using non probability sampling with purposive sampling technique. The method used a quantitative and using SmartPLS 4.0 for data analysis. The result showed conformity and self-control have a positive effect on consumptive behavior. E-money and lifestyle have not significant effect on consumptive behavior. E-money, lifestyle and conformity have positive effect on self-control. Self-control can mediate electronic money usage and conformity on consumptive behavior. Self-control can’t mediate lifestyle on consumptive behavior